اختيارات ابن حزم ومفرداته في باب الأسماء والأحكام، مبحث مفهوم الإيمان دراسة تحليلية نقدية: Ibn Hazm’s Selections and Unique Views in the Chapter of al-Asmāʾ wa-al-Aḥkām Topic: The Concept of Faith An Analytical and Critical Study - kais, Saidi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول هذا البحث اختيارات ابن حزم العقدية في باب مفهوم الإيمان، بوصفه أحد أهم مباحث باب الأسماء والأحكام، وتهدف هذه الدراسة إلى الوقوف على الأدلة التي بنى عليها ابن حزم اختياراته هذه، ولتحقيق هذا الهدف اعتمدت هذه الدراسة المنهج الاستقرائي التحليلي القائم على تتبع مقالات ابن حزم في هذا الباب، ثم تحليلها ومقارنتها بمقالات سائر المذاهب والفرق الإسلامية، وقد توصلت هذه الدراسة إلى نتائج مهمة، منها أن ابن حزم بِحُكْمِ كونه أحد حفاظ الحديث، فإنه ينسب نفسه في باب العقيدة إلى مذهب الصحابة والتابعين ومن اتبعهم من أهل الحديث والفقه، ولذلك فإنه يورد نصوص أقوالهم المشهورة مقراً لها إجمالا، غير أن شخصيته الاجتهادية تبرز عند تفصيله وشرحه لهذه الأقوال، فيقوم في بعض الأحيان بتقييد مطلق أقوالهم أو يخصص عمومها، أو يتأول بعض عباراتهم بحسب ما يمليه عليه نظره واجتهاده، وهذا يكشف نبذه للتقليد وميله إلى الاجتهاد والنظر في مباحث العقيدة، فهو يختار القول الذي ينصره الدليل بحسب رأيه، وكمثال على ذلك، فإن ابن حزم قد نقل قول أهل الحديث في تعريف الإيمان بأنه: تصديق بالقلب وقول باللسان وعمل بالجوارح، يزيد بالطاعة وينقص بالمعصية، وقد قَبِلَ وأقر ابن حزم هذا التعريف إجمالا، ولكنه عند شرحه له ذهب إلى أن عمل الجوارح ليس ركنا في الإيمان، وأن تصديق القلب لا يزيد ولا ينقص، وهذا مخالف لما اتفق عليه أهل الحديث من أن العمل ركن في الإيمان وأن تصديق القلب يزيد وينقص. ABSTRACT This research addresses Ibn Hazm’s theological choices regarding the concept of faith, as one of the most important topics within the domain of al-Asmāʾ wa-al-Aḥkām (Appellation and Rulings). The study aims to identify the evidence upon which Ibn Hazm based these choices. To achieve this objective, the study adopted an inductive-analytical methodology based on tracing Ibn Hazm’s opinions on this subject, then analysing and comparing them with the views of other Islamic schools of thought and sects. The study has reached important conclusions, among them is that Ibn Hazm, by virtue of being a hadith scholar (ḥuffāẓ), aligns himself in matters of creed with the school of the Companions, the Successors, and those who followed them among scholars of hadith and Fiqh. Therefore, he generally cites their well-known statements, affirming them in principle. However, his distinctive scholarly personality, rooted in independent reasoning (ijtihad), emerges when he elaborates upon and explains these statements. He sometimes restricts their absolute statements, or he specifies their generalities, or interprets some of their expressions according to what his own ijtihad dictates. This reveals his inclination towards applying independent reasoning in theological discussions, as he selects the view that, in his opinion, is supported by the evidence. As an example, Ibn Hazm transmitted the statement of scholars of Hadith defining faith as: affirmation by the heart, utterance by the tongue, and deeds, which increases with obedience and decreases with disobedience. While Ibn Hazm accepted and affirmed this definition in principle, in his detailed explanation, he argued that deeds are not one of pillar of faith, and that the affirmation of the heart neither increases nor decreases. This differs from what the scholar of Hadith have agreed upon: that deeds are a pillar of faith and that the heart’s affirmation does increase and decrease.